Lost in place : on place theory and landscape architecture - Kjerrgren, Lovisa (SLU/Dept. of Urban and Rural Development, 2015)
Place is on the one hand a commonsense everyday word with diversely connotative meanings, and on the other a contested concept with different interpretations across a broad range of academic disciplines and discourses. This thesis researches theories of place and their implications for the theory and design practice of landscape architecture. Responding to problems of insufficient theoretical grounding and inconsistent use of the concept of place within the discipline presently, it argues the need for a theory of place better articulated in relation to landscape architecture. It seeks to contribute to such theory formation by drawing on ideas from related disciplines – tracing diverse understandings of place beyond the commonsense meanings of the word and into the deeper reaches of place theory as tools to explain physical, social and spiritual aspects of the environment, and human relationships with it. Based on literature studies, four theoretical paradigms of place are synthesized and outlined (place as natural essence; place as experiential phenomenon; place as relational construct; and place as assemblage), and their implications and relevance for landscape architecture are analyzed through a framework of principles, processes, and contemporary tendencies of the discipline. A case study of a derelict wool store in Melbourne, Australia, is used as an example to illustrate and reflect upon the different theoretical views. The research shows that different theoretical understandings of place serve to frame and impact on the design process and its outcome in multiple ways, as well as condition the professional identity of landscape architects. It suggests that a contemporarily relevant understanding of place within landscape architecture reconciles a phenomenological and relational perspective, and regards place as four-dimensional.